Retorika Moderasi Beragama di Kawasan Perbatasan: Penelusuran, Praktek, atau Sebatas Retorika di Aceh Tenggara - Hanifah, Maria (YASIN, 2024)
Rhetoric of Religious Moderation is the art of speaking in implementing a moderate society. Religious moderation illustrates that moderation is not only carried out by Muslims but is carried out by all religions. The aim of this research is to determine the form/practice of religious moderation and its implications within the Ministry of Religion. The research method used is a mixed-method type, concurrent embedded. The analysis used is Miles and Huberman's as well as Quantitative Percentage analysis. The research samples used were the Southeast Aceh Ministry of Religion, KUA, Religious Counselors, FKUB, and the Community. The forms/practices of moderation that are already underway within the Ministry of Religion of Aceh Tenggara include a society that has a national commitment, a society that is non-violent, a society that accepts religious traditions, and a society that is tolerant. Religious moderation which is running in the "Good" category, namely 88%, is already running. The implications of the practice of religious moderation within the Ministry of Religion of Southeast Aceh are more about the task of protecting the community to implement Religious Moderation or making a moderate society still encounter several difficulties, namely 1) Religious Moderation outside Southeast Aceh among Non-Muslims must be emphasized, 2) The identity of the Catholic religion on the KTP is clarified, 3) Emphasis on religious sharia/teachings for border students is increased, 4) Provision of adequate educational facilities in border areas, 5) Increased justice for all citizens in practicing religion and receiving religious education, 6) Programming of religious instructors who maximum and effective.